MEDICAL ENGLISH AS A TOOL FOR PROFESSIONAL DEVELOPMENT (Ustozlar uchun, 2026)
Medical English plays a crucial role in the professional development of healthcare workers in today’s globalized world. It enables doctors, nurses, and medical students to access international research, communicate with foreign colleagues, and provide better patient care. Knowledge of Medical English improves understanding of medical terminology, clinical guidelines, and modern treatment methods. Moreover, English proficiency opens opportunities for career growth, participation in international conferences, and continuing medical education. This article discusses the importance of Medical English as a key tool for professional development, highlights its practical benefits in healthcare practice, and emphasizes the need for integrating Medical English into medical education systems.